Stage-dependent dynamics of Apolipoprotein C3 across the spectrum of MASLD - Eva Katharina Messer; Janett Fischer; Toni Herta; Albrecht Boehlig; Madlen Matz-Soja; Adrienn Tuennemann-Tarr; Susanne Gaul; Ulrich Laufs; Thomas Berg (PLoS ONE, 2026)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is a systemic disorder closely linked to cardiometabolic risk and dysregulated lipid metabolism. Apolipoprotein C3 (ApoC3), a key regulator of triglyceride-rich lipoproteins and mediator of cardiovascular disease, has been implicated in hepatic steatosis. However, its stage-specific role across the MASLD spectrum remains incompletely defined. Methods In this cohort study, serum ApoC3 concentrations were quantified in 197 patients with MASLD across different disease stages (non-fibrotic MASLD, fibrosis, cirrhosis, and cirrhosis with hepatocellular carcinoma (HCC)) and compared with 204 blood donor controls. Associations with metabolic parameters, non-invasive fibrosis markers, histology, cardiometabolic comorbidities, and genetic risk variants were analyzed. Results ApoC3 levels exhibited a stage-dependent pattern, with significantly lower concentrations in cirrhotic MASLD and HCC compared to non-fibrotic MASLD and controls (median 18.7 vs. 26.6 vs. 27.4 mg/dL, p < 0.05). Lower ApoC3 levels were associated with markers of advanced liver disease, including higher bilirubin, liver stiffness, Fibrosis-4 index, and NAFLD fibrosis score. In contrast, higher ApoC3 levels were observed in early-stage MASLD and were associated with cardiometabolic comorbidities and dyslipidemia. ApoC3 correlated positively with triglycerides (r = 0.485, p < 0.001) and controlled attenuation parameter values (r = 0.274, p = 0.004), and was highest in patients with severe steatosis (S3) and increased inflammatory activity (NAS ≥ 5). Diagnostic performance for cirrhosis was modest (AUC 0.642) and for HCC 0.673. Conclusion ApoC3 demonstrates a biphasic, stage-dependent profile in MASLD, with elevated levels reflecting hepatic steatosis, and metabolic dysfunction in early disease, and declining levels likely indicating impaired hepatic function in advanced stages. These findings position ApoC3 as a link between hepatic lipid accumulation and cardiovascular risk rather than a linear marker of disease severity. Its clinical utility may lie in integrative, multi-parameter models rather than as a standalone biomarker.